The older the better: are elderly study participants more non-representative? A cross-sectional analysis of clinical trial and observational study samples. Issue 6 (14th December 2012) - Golomb, Beatrice A; Chan, Virginia T; Evans, Marcella A; Koperski, Sabrina; White, Halbert L; Criqui, Michael H
Abstract : Objective: Study participants can differ from the target population they are taken to represent. We sought to investigate whether older age magnifies such differences, examining age-trends, among study participants, in self-rated level of activity compared to others of the same age. Design: Cross-sectional examination of the relation of participant age to reported 'relative activity' (ie, compared to others of the same age), a bidirectionally correlated proxy for relative vitality, in exemplars of randomised and observational studies. Setting: University of California, San Diego (UCSD) Participants: 2404 adults aged 40–79 including employees of UCSD, and their partners (San Diego Population Study, observational study). 1016 adults (aged 20-85) not on lipid medications and without known heart disease, diabetes, cancer or HIV (UCSD Statin Study, randomised trial). Measurements: Self-rated activity relative to others' age, 5-point Likert Scale, was evaluated by age decade, and related via correlation and regression to a suite of health-relevant subjective and objective outcomes. Results: Successively older participants reported successively greater activity relative to others of their age (greater departure from the norm for their age), p<0.001 in both studies. Relative activity significantly predicted (in regression adjusted for age) actual activity (times/week exercised), and numerous self-rated and objective health-predictors. These included general self-rated health, CES-D (depression score), sleep, tiredness, energy; body mass index, waist circumference, serum glucose, high-density lipoprotein-cholesterol, triglycerides and white cell count. Indeed, some health-predictor associations with age in participants were 'paradoxical, ' consistent with greater apparent health in older age—for study participants. Conclusions: Study participants may not be representative of the population they are intended to reflect. Our results suggest that departures from representativeness may be amplified with increasing age. Consequently, the older the age, the greater the disparity may be between what is recommended based on 'evidence, ' and what is best for the patient. Trial Registration: UCSD Statin Study—Clinicaltrials.gov # NCT00330980 (http://ClinicalTrials.gov )